CORPORATE GOVERNANCE, CAPITAL INTENSITY AND FINANCIAL DISTRESS ON ACCOUNTING CONSERVATISM: THE MODERATING ROLE OF LEVERAGE - Gusmi, Dedek; Nurlita, Anna (Jurnal Akuntansi dan Keuangan (JAK), 2025)
This study aims to analyze the effect of corporate governance, capital intensity, and financial distress on accounting conservatism with leverage as a moderating variable. This study uses a quantitative approach on 18 insurance companies listed on the Indonesia Stock Exchange during the 2021–2023 period, with a total of 54 observational data obtained through a purposive sampling method. Secondary data were obtained from financial reports and analyzed using panel data regression and Moderating Regression Analysis (MRA) using EViews 12 software. The results of the study indicate that partially, institutional ownership, managerial ownership, independent commissioners, capital intensity, and financial distress do not have a significant effect on accounting conservatism (p > 0.05). The results of the MRA test also show that leverage is unable to moderate the effect of institutional ownership, managerial ownership, independent commissioners, and capital intensity on accounting conservatism. However, leverage is proven to weaken the effect of financial distress on accounting conservatism (β = -0.0377 p < 0.05). The coefficient of determination (R²) value of 0.4456 shows that the independent variable is able to explain accounting conservatism by 44.56%, while the remainder is influenced by other factors outside the research model.